Enterotoxigenic Escherichia coli infection of weaned pigs: Intestinal challenges and nutritional intervention to enhance disease resistance - Kim, Kwangwook; Song, Minho; Liu, Yanhong; Ji, Peng (Frontiers in Immunology, 2022)
Enterotoxigenic Escherichia coli (ETEC) infection induced post-weaning diarrhea is one of the leading causes of morbidity and mortality in newly weaned pigs and one of the significant drivers for antimicrobial use in swine production. ETEC attachment to the small intestine initiates ETEC colonization and infection. The secretion of enterotoxins further disrupts intestinal barrier function and induces intestinal inflammation of weaned pigs. ETEC infection can also aggravate the intestinal microbiota dysbiosis due to weaning stress and increase the susceptibility of weaned pigs to other enteric infectious diseases, which may result in diarrhea or sudden death. Therefore, the amount of antimicrobial drugs for medical treatment purposes in major food-producing animal species is still significant. The alternative practices that may help reduce the reliance on such antimicrobial drugs and address animal health needs are highly demanded. Nutritional intervention in order to enhance intestinal health and the overall performance of weaned pigs is one of the most powerful practices in the antibiotic-free production system. This review summarizes the utilization of several categories of feed additives or supplements, such as direct-fed microbials, prebiotics, phytochemicals, lysozyme, and micro minerals in newly weaned pigs. The current understanding of these candidates on intestinal health and disease resistance of pigs under ETEC infection are particularly discussed, which may inspire more research on the development of alternative practices to support food-producing animals.